Involvement of the GABAergic system in the anxiolytic-like effect of the flavonoid ellagic acid in mice - Girish, Chandrashekaran; Raj, Vishnu; Arya, Jayasree; Balakrishnan, Sadasivam (European journal of pharmacology, 2013)
Anxiolytic-like effects of dietary flavonoids are relatively well known. Ellagic acid is a naturally occurring flavonoid compound which is abundant in many plants and fruits. The present study was designed to investigate the antianxiety-like effect of ellagic acid in mice using an elevated plus-maze test. The involvement of the GABAergic and serotonergic systems in the antianxiety-like activity of ellagic acid was also studied. Our results showed that ellagic acid treatment (25, 50 and 100mg/kg, p.o.), produced a significant increase in the percentage of time spent and entry into the open arms, with a profile comparable to that of diazepam (1mg/kg, p.o.). Unlike diazepam, the anxiolytic doses of ellagic acid did not prolong the duration of sodium thiopental-induced loss of righting reflex, indicating that this flavonoid is non-hypnotic. The anxiolytic effect observed with ellagic acid treatment (25mg/kg, p.o.) was antagonized by pretreatment with picrotoxin (a non-competitive GABAA receptor antagonist, 1mg/kg, i.p.) and flumazenil (a benzodiazepine site antagonist, 1mg/kg, i.p.) but not with p-chlorophenylalanine (a serotonin synthesis inhibitor, 100mg/kg, i.p.) and pindolol (a β-adrenoceptors blocker/5-HT1A/1B receptor antagonist, 10mg/kg, i.p.). Taken together, the data demonstrated that acute and chronic administration of ellagic acid to mice has produced antianxiety-like effect when tested in the elevated plus-maze. The experiments with different receptor blockers suggest an involvement of GABAergic system in the anxiolytic action of this bioflavonoid. However, this action is not seems to be mediated through serotonergic system. [Display omitted]